Figurative Language Analysis In Album Evolve By Imagine Dragons - Syinthia Az-Zahra; Euis Kurniasih; Myta Widyastuti (University of Darussalam Gontor, 2022)
Figurative language is commonly found in literary works, such as a song. The purpose of this research is to analyze the types and meanings of figurative language used in Imagine Dragons’ album Evolve. The research used descriptive qualitative. The theory used is from Mezzo (1999) which divided figurative language into three categories; comparison type (Metaphor, Simile, and Personification), substitution type (Metonymy and Synecdoche), and exaggeration type (Hyperbole and Litotes). The result indicated that there are 100 lines of lyrics that contain figurative language in the Evolve album. They are metaphor (23%), simile (8%), personification (15%), metonymy (36%), synecdoche (2%), hyperbole (10%), and litotes (6%). The most dominant type of figurative language in Evolve's album is metonymy with 36 lines and metaphor with 23 lines. Metonymy became most used in the album Evolve which represents explicit content that imagines a character or object in the album Evolve, while metaphor became the second most used figurative language in Evolve album to make the ideas of the lyrics more meaningful, imaginative, and interesting for the listener.